ICERI2016 Proceedings 2016
DOI: 10.21125/iceri.2016.1916
|View full text |Cite
|
Sign up to set email alerts
|

Lesson Based Professional Development: Helping Primary Teachers Teach 21st Century Skills

Abstract: In the context of planned curriculum reforms in Latvia, teachers will have to acquire the necessary understanding and experience for teaching 21 st century skills. This goal demands real changes in lesson design and how teaching is presented in the classroom. Therefore, this paper seeks to describe and analyse two years of experience in implementing a lesson-based professional learning model for primary school teachers. Empirical data were gathered through a case study design documenting the experience and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
1
0
4
Order By: Relevance
“…Besides, teachers felt that 21st century learning is suitable for certain subjects, and they do not know how to use these features for assessment student performance in learning. Namsone, Cakane, France, and Butkevica (2016), study found that teachers understood better after a professional development model as a guide.…”
Section: Discussionmentioning
confidence: 88%
“…Besides, teachers felt that 21st century learning is suitable for certain subjects, and they do not know how to use these features for assessment student performance in learning. Namsone, Cakane, France, and Butkevica (2016), study found that teachers understood better after a professional development model as a guide.…”
Section: Discussionmentioning
confidence: 88%
“…Skolotāju profesionālās mācīšanās modeļa struktūra (adaptēts pēc Namsone, Čakāne, France, & Butkēviča, 2016) Pētījumā bija iesaistītas skolotāju komandas no 13 skolām. Katru komandu veidoja divi sākumskolas posma skolotāji un skolas vadības pārstāvis.…”
Section: Sadarbība Skolas Komandāunclassified
“…Modeļa aprobācija apstiprina skolas komandas un vadības lielo ietekmi uz individuāla skolotāja profesionālo izaugsmi (Namsone, Čakāne, France, & Butkēviča, 2016).…”
Section: Sadarbība Skolas Komandāunclassified
See 1 more Smart Citation
“…Skolotāju profesionālās mācīšanās modeļa struktūra (adaptēts pēc Namsone, Čakāne, France, & Butkēviča, 2016) Pētījumā bija iesaistītas skolotāju komandas no 13 skolām. Katru komandu veidoja divi sākumskolas posma skolotāji un skolas vadības pārstāvis.…”
Section: Sadarbība Skolas Komandāunclassified